2019
DOI: 10.1002/jms.4364
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down mass spectrometry of intact phosphorylated β‐casein: Correlation between the precursor charge state and internal fragments

Abstract: Phosphorylated proteins play essential roles in many cellular processes, and identification and characterization of the relevant phosphoproteins can help to understand underlying mechanisms. Herein, we report a collision‐induced dissociation top‐down approach for characterizing phosphoproteins on a quadrupole time‐of‐flight mass spectrometer. β‐casein, a protein with two major isoforms and five phosphorylatable serine residues, was used as a model. Peaks corresponding to intact β‐casein ions with charged state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Kelleher and co-workers showed that internal fragments from CID fragmentation of the common test protein, ubiquitin (8.6 kDa), can be assigned to result in significantly greater protein sequence coverage [21]. Similarly, for other intact proteins, the inclusion of internal fragments that can be generated by CID could result in greater explanation of the protein sequence [27,28]. Our laboratory demonstrated that internal product ions can be generated from top-down MS of large, native protein complexes [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelleher and co-workers showed that internal fragments from CID fragmentation of the common test protein, ubiquitin (8.6 kDa), can be assigned to result in significantly greater protein sequence coverage [21]. Similarly, for other intact proteins, the inclusion of internal fragments that can be generated by CID could result in greater explanation of the protein sequence [27,28]. Our laboratory demonstrated that internal product ions can be generated from top-down MS of large, native protein complexes [29].…”
Section: Introductionmentioning
confidence: 99%
“…20 Similarly, for other intact proteins, the inclusion of internal fragments that can be generated by CID could result in greater explanation of the protein sequence. 27,28 Our laboratory demonstrated that internal product ions can be generated from top-down MS of large, native protein complexes. 29 These examples suggest that the inclusion of internal fragments in top-down protein sequencing experiments could significantly enhance the protein sequence coverage and the efficiency of top-down mass spectrometry experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A key advantage to top down proteomic (TDP) methods, is the opportunity to localise PTMs within proteins. [93][94][95] This approach has recently been employed to identify the region of phosphorylation (between the 14 th and 50 th AA residue) for commercially obtained cow βcasein sprayed from denaturing solution conditions, 96 although this approach would also fit within our native MS workflow. 97 The fragmentation map highlights the fragments produced from the [M+Ca+Na+5H] 8+ ion subjected to 145V HCD CE.…”
Section: The Use Of Hcd To Validate Protein Identificationmentioning
confidence: 99%
“…53 While the analysis of internal fragment ions has been largely ignored by the TD-MS community due to the general lack of software tools to accurately and reliably assign them, the concept of the formation of internal fragment ions in TD-MS spectra is not novel. Previous studies have shown that the inclusion of internal fragments results in much richer sequence information of small peptides, 51,[54][55][56][57] intact proteins, [58][59][60][61][62][63][64] protein complexes, 65,66 and aid the identification of ambiguous proteoforms in mammalian cell lysates by topdown ptoteomics. 67 In addition, a recent study by Chin et al demonstrated the utility of internal fragments to enhance sequence coverage and to decipher disulfide bonds of disulfide-rich peptides.…”
Section: Introductionmentioning
confidence: 99%